Switzerland’s Dependence on a Diamorphine Monopoly - Schmitt-Koopmann, Caroline; Baud, Carole-Anne; Junod, Valérie; Simon, Olivier (Frontiers in Psychiatry, 2022)
In 2021, the manufacturer of diamorphine reported a possible impending shortage for Switzerland and Germany. This led us to investigate this controlled medicine’s manufacture, market, and regulatory constraints. Based on our analysis of legal texts and gray literature in the form of reports and documents, we propose recommendations to prevent and address diamorphine shortages in Switzerland. Diamorphine, also known as pharmaceutical “heroin,” is used medically to treat persons with severe opioid use disorder in a handful of countries. The controlled medicine is manufactured from morphine, which, in turn, is extracted from opium poppies. Studying data from the International Narcotics Control Board for 2019, we find that Switzerland accounts for almost half of the worldwide medical consumption of diamorphine. It manufactures more than half of the worldwide total and keeps the largest stocks. Moreover, Switzerland is dependent on a sole supplier of diamorphine (monopoly). As a niche product, diamorphine has an increased risk of shortage. Such a shortage would immediately threaten a valuable public health program for around 1,660 Swiss patients. We believe it is urgent to curtail the monopoly and ensure a stable supply for the future.